Opportunities and Benefits of Football for Students - Qurbonovich, Baxtiyor Amanturdiyev (European Journal of Life Safety and Stability (2660-9630), 2021)
There is a lot of information about the history of the game of football and, in particular, its rules. The composition of football teams and their structural structure, their functions. About the tactical structure of team members, their functions and tasks.